Radioprotective effect of curcuma longa extract on γ-irradiation-induced oxidative stress in rats - Nada, A.; Hawas, A.; Amin, N.; Elnashar, Magdy; Abd Elmageed, Z. (2012)
This study was conducted to evaluate the modulatory effect of aqueous extract of Curcuma longa (L.) against girradiation (GR), which induces biochemical disorders in male rats. The sublethal dose of GR was determined in primary hepatocytes. Also, the effect of C. longa extract was examined for its activity against GR. In rats, C. longa extract was administered daily (200 mg/kg body mass) for 21 days before, and 7 days after GR exposure (6.5 Gy). The lipid profile and antioxidant status, as well as levels of transaminases, interleukin-6 (IL-6), and tumour necrosis factor a (TNFa) were assessed. The results showed that in hepatocytes, the aqueous extract exhibited radioprotective activity against exposure to GR. Exposure of untreated rats to GR resulted in transaminase disorders, lipid abnormalitie, elevation of lipid peroxidation, trace element alterations, release of IL-6 and TNF, and decrease in glutathione and protein level of superoxide dismutase-1 (SOD-1) and peroxiredoxin-1 (PRDX-1). However, treatment of rats with this extract before and after GR exposure improved antioxidant status and minimized the radiation-induced increase in inflammatory cytokines. Changes occurred in the tissue levels of trace elements, and the protein levels of SOD-1 and PRDX-1 were also modulated by C. longa extract. Overall, C. longa exerted a beneficial radioprotective effect against radiation-induced oxidative stress in male rats by alleviating pathological disorders and modulating antioxidant enzymes.